Analysis Of The Role Of Social Media In Political Marketing Of The National Mandate Party In The 2024 General Election In Jambi City - Dwi P kusuma; Deshinta C Pertiwi; Rima Rismarwanti; Brian H Sinulingga; Ian Pasaribu (Penerbit Jurnal Indonesia, 2024)
In the world of politics, the use of social media can also be an opportunity for new political parties to introduce their parties to the public. Political marketing via social media nowadays is one of the effective marketing techniques used by a number of political actors and political parties in Indonesia, especially for new political parties, because social media can make it easier to disseminate information related to the political party. This study used qualitative research methods. The aim is to explain the phenomenon in as much detail as possible through data collection and the object of this research includes the Jambi City National Mandate Party. The method used in this research is a literature review. Literature review is a systematic process of collecting, evaluating, and synthesizing literature related to a particular research topic. Data collection and documentation techniques from Google Schoolar. Data analysis and critical review techniques. Critical review is a process of critical evaluation and analysis of a particular work or topic. Political marketing strategies teach parties to be able to differentiate their political products and image through the political marketing process. There are 4 marketing mixes in the world of politics, namely: Product, Promotion, Price, Placement.